Analisis Penyalahgunaan Kekuasaan dari Pejabat Kemenkeu yang Dilakukan oleh Rafael Alun Trisambodo - Erlisya, Vyona; Aulia, Aisyah; Tobing, Naomi Boru; Saputra, Bagas (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Although Indonesia has adopted advanced technology that is expected to improve efficiency and transparency, corruption cases such as the one involving Rafael Alun show that corruption is still a significant problem. So today there are still many people who abuse it just to give themselves satisfaction. Like the case of Mario Dandy who exposed the persecution of David, so that this case dragged Mario's parents, Rafael Alun. In this case Mario dandy's case became more complex which led to the revelation of Rafael alun who was involved in a graft case that he did for 12 years which reached 16.6 billion and money laundering cases.